Free-standing three-dimensional carbon nanotubes/amorphous MnO2 cathodes for aqueous zinc-ion batteries with superior rate performance. (December 2020) - Bi, S.; Wu, Y.; Cao, A.; Tian, J.; Zhang, S.; Niu, Z.
Abstract: Rechargeable aqueous zinc-ion batteries (ZIBs) have gained particular attention in recent years because of their low cost and high safety. However, most of their performances are limited by unsatisfied architecture of cathodes. In addition, the degree of crystallinity of active materials also plays an important role in their electrochemical performance. Herein, we fabricated free-standing composite films with amorphous MnO2 (a-MnO2 ) and carbon nanotubes (CNTs) by an in situ deposition method. The free-standing a-MnO2 @CNTs composite films can directly serve as the cathodes of ZIBs without binder and current collector. The resultant cathode exhibits highly electrical conductivity and fast ion-diffusion because of the corporation of interconnected three-dimensional CNTs architectures and ultra-thin a-MnO2 nanosheets. As a result, the resultant ZIB displays high energy and power density, as well as stable cycling performance. Moreover, based on composite films, flexible ZIBs were constructed, and they could remain stable electrochemical performance under different bending states, which have great potential for the application in flexible and wearable electronics. Graphical abstract: Free-standing three-dimensional (3D) carbon nanotubes/amorphous MnO2 composite films were prepared as cathodes of aqueous ZIBs. The incorporation of amorphous MnO2 nanosheets and interconnected CNT 3D conductive architecture enables the resultant cathodes with fast ion-diffusion and highly electrical conductivity. Based on these cathodes, the fabricated ZIBs display high energy and power densities, as well as long cycling performance. Image 1 Highlights: Free-standing composite films were prepared as the cathodes of aqueous zinc-ion batteries. The resultant aqueous Zn/MnO2 batteries exhibit superior rate performance. Flexible Zn/MnO2 batteries remain stable performance under bending states.